THE INFLUENCE OF PRICE PERCEPTION, E-WOM, BRAND AMBASSADOR, AND HALAL LABELING ON ARTHA LDT SKINCARE PURCHASING DECISIONS THROUGH BUYER INTEREST IN BESUKI SITUBONDO - Sofiyatul Madaniyah; Khamdan Rifa’i; Nurul Widyawati Islami Rahayu (Adisam Publisher, 2025)
This study conceptually examines how price perception, electronic word of mouth (E‑WOM), brand ambassadors, and halal labeling influence purchase decisions for Artha LDT skincare products, with purchase intention serving as an intervening variable. The research context is Besuki, Situbondo, where local halal-certified skincare brands have grown through online marketplaces and social media. Using theoretical synthesis from consumer behavior, marketing communications, and halal consumer studies, this paper develops hypotheses and a conceptual path model. The analysis suggests that perceived affordability and price–quality fit positively shape purchase intention; E‑WOM and credible brand ambassadors amplify trust and perceived value; halal labeling reduces perceived consumption risk and strengthens intention among Muslim consumers. Purchase intention mediates the relationship between the antecedents and actual purchase decision. Contributions include a contextualized model for halal skincare marketing and practical recommendations for MSME brands aiming to scale through digital channels.